Resilience metrics and measurement methods for transportation infrastructure: the state of the art - Sun, Wenjuan; Bocchini, Paolo; Davison, Brian D. (Sustainable and resilient infrastructure, 2020)
Transportation infrastructure plays an important role in supporting the national economy and social well-being. Extreme events have caused terrible physical damages to the transportation infrastructure, with long-term socioeconomic impacts. An increasing number of studies focus on the resilience analysis of transportation infrastructure to support planning and design, as well as efficient management. As a comprehensive review, this paper covers different metrics for resilience assessments, with discussions of fundamental challenges due to uncertainties and interdependencies. It points out that validations of resilience assessments are limited due to the general scarcity of data, which may hinder practical applications. Finally, directions for future research are suggested. This paper provides an organized overview of the many lines of research in the field, accomplishments, and open gaps. It indicates useful starting points for researchers new to this field, and serves as a reference for teams already active on this topic.